2011
DOI: 10.1098/rspb.2011.1697
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofBRCA1andBRCA2mutations on female fertility

Abstract: Women with BRCA1/2 mutations have a significantly higher lifetime risk of developing breast or ovarian cancer. We suggest that female mutation carriers may have improved fitness owing to enhanced fertility relative to non-carriers. Here we show that women who are carriers of BRCA1/2 mutations living in natural fertility conditions have excess fertility as well as excess post-reproductive mortality in relation to controls. Individuals who tested positive for BRCA1/2 mutations who linked into multi-generational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 32 publications
1
79
1
Order By: Relevance
“…Likewise, glucose metabolism may also mediate the survival costs of having many sons, as diabetic mothers are found to overproduce sons [26], but they may also suffer from reduced lifespan [27]. By contrast, a recent genetic study has suggested that women who are carriers of the BRCA1/2 mutation may produce proportionally fewer sons [28] and have higher post-reproductive mortality [29]. Given the complexity of phenotypic associations reported in the literature [16], there is thus a need to understand the underlying biological and social mechanisms linking offspring sex composition to parental survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, glucose metabolism may also mediate the survival costs of having many sons, as diabetic mothers are found to overproduce sons [26], but they may also suffer from reduced lifespan [27]. By contrast, a recent genetic study has suggested that women who are carriers of the BRCA1/2 mutation may produce proportionally fewer sons [28] and have higher post-reproductive mortality [29]. Given the complexity of phenotypic associations reported in the literature [16], there is thus a need to understand the underlying biological and social mechanisms linking offspring sex composition to parental survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study concluded that BRCA1 germ-line mutations may be associated with reserved ovarian reserve (5). Another study investigated the effects of BRCA1 and BRCA2 mutations on female infertility (13). Finally, a recent study (14) reported that patients with BRCA gene mutations showed a normal ovarian response in IVF compared to patients with no BRCA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, grandmothers may increase the fertility of all their offspring. A study of the life histories of Finnish and Canadian women living in farming communities in the eighteenth and nineteenth centuries shows that for every year of survival beyond age 50 a woman produced an extra 0.2 grandchildren by reducing her daughters' birth intervals and increasing the survival of her grandchildren [12].In the Smith et al study [4], fertilities and childhood survival would have been affected by any grandmother effect present. However, this effect appears to have been small, judging from survival rates of children born to women in the pre-1930 cohort, which are marginally higher for carriers (94%), who had a lower probability of having a living grandmother, than controls (92%).…”
mentioning
confidence: 98%
“…However, there is some risk of developing these cancers before menopause, and the moderate negative selection that this generates, together with the recurrence of the alleles due to mutation, has been used to explain the frequency of BRCA1 mutations of 1 in 3000 women in the USA [3]. However, a recent study showing that BRCA1/ 2 mutations increase female fertility (number of children born) by nearly 50 per cent [4] demands a reanalysis of the selection operating on these alleles. Smith et al…”
mentioning
confidence: 99%
See 1 more Smart Citation